The Effects of Students Team Achievement Division (STAD) to Improve Students’ Achievement in Writing Skill - carli baka (UKI TORAJA, 2016)
Charlie Baka. The Effects of Students Team Achievement Division (STAD) to Improve Students’Achievement in Writing Skill (Supervised by Kisman Salija and Murni Mahmud)The objectives of this research are (1) to find out whether the use of Students Team AchievementDivision (STAD) improve students’ achievement in writing skill (2) to find out whether the use ofSTAD motivate the students in learning writing skill at fourth semester of English department of UKIToraja. This research employed quasi-experimental design. It used two groups, one received treatmentSTAD and the other group received GI. The subjects of this research were class F and G were takenrandomly. Class F as the experimental group and class G as control group consisted of 30 students.The data of this research was collected through writing test and questionnaire. The results of thisresearch were (1) The use of STAD has effects to improve the writing achievement of the fourthsemester students of UKI Toraja in experimental class. (2) The motivations of the fourth semesterstudents of UKI Toraja as experimental class showed a great positive in learning writing by usingSTAD. So, it can be concluded that the use of STAD motivated the students in writing and agreed touse of STAD because it could built students’ confidence and finding ideas. Many students also agreedthat the use of STAD was interested in work group session.